2005
DOI: 10.1016/j.jmr.2004.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of pseudo pure states: the role of cross-correlations

Abstract: In Quantum Information Processing by NMR one of the major challenges is relaxation or decoherence. Often it is found that the equilibrium mixed state of a spin system is not suitable as an initial state for computation and a definite initial state is required to be prepared prior to the computation. As these preferred initial states are non-equilibrium states, they are not stationary and are destroyed with time as the spin system relaxes toward its equilibrium, introducing error in computation. Since it is not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…While standard schemes for pseudopure state preparation involve a large number of experiments and lead to reduced signal, recently a few schemes have been proposed that use only one ancilla spin and fewer number of experiments [52,53]. The relaxation behavior of twospin pseudopure states have been investigated and it was noted that cross-correlated spin relaxation plays an important role in accelerating or retarding the lifetimes of such states [54]. The relaxation of pseudopure states in an oriented spin-3/2 system has been described using Redfield theory and reduced spectral densities [55].…”
Section: B State Initialization Schemesmentioning
confidence: 99%
“…While standard schemes for pseudopure state preparation involve a large number of experiments and lead to reduced signal, recently a few schemes have been proposed that use only one ancilla spin and fewer number of experiments [52,53]. The relaxation behavior of twospin pseudopure states have been investigated and it was noted that cross-correlated spin relaxation plays an important role in accelerating or retarding the lifetimes of such states [54]. The relaxation of pseudopure states in an oriented spin-3/2 system has been described using Redfield theory and reduced spectral densities [55].…”
Section: B State Initialization Schemesmentioning
confidence: 99%
“…Therefore, it is important to investigate relaxation in the context of NMR quantum computing. References [26] and [27] reports a spinlattice relaxation study of various NMR quantum computing coherent states.…”
Section: Nmr Quantum Logic Gatesmentioning
confidence: 99%
“…Besides, NMR coherences vanish in a time T 2 , the transverse relaxation time. Regarding relaxation studies of pseudo-pure states in the context of NMR quantum information processing, one can point out the studies reported on references [11,12,13,18]. In those studies, relaxation behavior of various pseudopure states have been investigated in different NMR systems.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [12] it was found that whereas cross-correlations accelerate the relaxation of certain pseudo-pure states, they delay that of others. On the other hand, a robust method for quantum process tomography provided a set of Lindblad operators that optimally fit the density matrices measured at a sequence of time points [13].…”
Section: Introductionmentioning
confidence: 99%